1996
DOI: 10.3758/bf03199012
|View full text |Cite
|
Sign up to set email alerts
|

Value transfer in concurrent-schedule discriminations by pigeons

Abstract: When pigeons are trained on a discrete-trial simultaneous discrimination, some of the value associated with the positive stimulus appears to transfer to the negative stimulus (Zentall & Sherburne, 1994). Pigeons preferred a negative stimulus that had been discriminated from an always-positive stimulus (S +) over a negative stimulus that had been discriminated from a sometimes-positive stimulus (S~). A very different finding (suggestive of transitivity of preference or contrast) was reported by Belke (1992). On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…greater value through its association with A than D acquires through its association with C. Design 2 is very similar to the Design I employed by Dorrance et al (1998), except that C is partially reinforced, and A is consistently reinforced within the context of the A-Band C-D discrimination (Clement, Weaver, Sherburne, & Zentall, 1998, Experiment 2;Zentall & Sherburne, 1994;Zentall, Sherburne, Roper, & Kraemer, 1996;Zentall, Weaver, & Sherburne, 1996). In Design 3, A is consistently reinforced, whereas discrimination training is given prior to the C-D trials in which C is consistently nonreinforced (Steirn, Weaver, & Zentall, 1995).…”
Section: Exp 1 Eexp 4(riy) Exp2 Oexp 4(rib)mentioning
confidence: 91%
See 1 more Smart Citation
“…greater value through its association with A than D acquires through its association with C. Design 2 is very similar to the Design I employed by Dorrance et al (1998), except that C is partially reinforced, and A is consistently reinforced within the context of the A-Band C-D discrimination (Clement, Weaver, Sherburne, & Zentall, 1998, Experiment 2;Zentall & Sherburne, 1994;Zentall, Sherburne, Roper, & Kraemer, 1996;Zentall, Weaver, & Sherburne, 1996). In Design 3, A is consistently reinforced, whereas discrimination training is given prior to the C-D trials in which C is consistently nonreinforced (Steirn, Weaver, & Zentall, 1995).…”
Section: Exp 1 Eexp 4(riy) Exp2 Oexp 4(rib)mentioning
confidence: 91%
“…With one exception (Dorrance et al, 1998, Experiment 4: RIB), the stimuli used in all studies discussed above were consistently paired red-yellow and blue-green (Clement et al, 1998, Experiment 2;Steirn et al, 1995;Zentall & Sherburne, 1994, Experiment 2;Zentall, Sherburne, et al, I996a;Zentall, Weaver,& Sherburne, 1996), other than the first experiment ofZentall and Sherburne's (1994) study, in which red-green and dot-circle pairings were used.' Although each stimulus was used equally frequently in each of the four roles (A, B, C, or D), the critical issue is whether generalization within each pair is greater than that between the pairs.…”
Section: Exp 1 Eexp 4(riy) Exp2 Oexp 4(rib)mentioning
confidence: 99%
“…When the pigeons were tested with a choice between two identical schedules that were from two different contexts in training, B (VI 40 sec) versus C (VI 40 sec), C was preferred. Grace and Savastano (1997) argued that although C elicited more responding than B, C may not have been more valued than B (see also Zentall, Weaver, & Sherburne, 1996). To test this hypothesis, Grace and Savastano separated the reinforcing value of the stimuli from their eliciting strength by using a concurrent-chains procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondence should be sent to T R. Zentall, Department of Psychology, University of Kentucky, Lexington, criminations, the pigeons were given a choice between the two negative stimuli (B and D). According to value transfer theory, A should have had more value to transfer to B than C should have had to transfer to D. In support of value transfer theory, Zentall and Sherburne found that animals trained in this manner consistently chose B over D. Subsequent research has validated this effect (e.g., Steirn, Weaver, & Zentall, 1995;Zentall, Sherburne, Roper, & Kraemer, 1996;Zentall, Weaver, & Sherburne, 1996).Recently, Clement, Weaver, Sherburne, and Zentall (1998) tested the second of Fersen et al's (1991) hypotheses, that negative value from the S -may transfer to its associated S+, resulting in a decrease in the relative value of the S+. Clement et al (1998) trained pigeons using a procedure similar to that used by Zentall and Sherburne (1994), but in this case, the values of the S+ stimuli were equated, whereas the values of the S-stimuli were varied (AIOOB o and ClOoD so)' In a preliminary experiment, they found that the value of the S-had little effect on the value of the S+ with which it was presented.…”
mentioning
confidence: 88%